Geographical distribution and oncogenic risk association of human papillomavirus type 58 E6 and E7 sequence variations1. Issue 11 (29th November 2012) - Chan, Paul K.S.; Zhang, Chuqing; Park, Jong‐Sup; Smith‐McCune, Karen K.; Palefsky, Joel M.; Giovannelli, Lucia; Coutlée, Francois; Hibbitts, Samantha; Konno, Ryo; Settheetham‐Ishida, Wannapa; Chu, Tang‐Yuan; Ferrera, Annabelle; et al.
Abstract: Human papillomavirus (HPV) 58 accounts for a notable proportion of cervical cancers in East Asia and parts of Latin America, but it is uncommon elsewhere. The reason for such ethnogeographical predilection is unknown. In our study, nucleotide sequences of E6 and E7 genes of 401 HPV58 isolates collected from 15 countries/cities across four continents were examined. Phylogenetic relationship, geographical distribution and risk association of nucleotide sequence variations were analyzed. We found that the E6 genes of HPV58 variants were more conserved than E7. Thus, E6 is a more appropriate target for type‐specific detection, whereas E7 is more appropriate for strain differentiation. The frequency of sequence variation varied geographically. Africa had significantly more isolates with E6‐367A (D86E) but significantly less isolates with E6‐203G, ‐245G, ‐367C (prototype‐like) than other regions ( p ≤ 0.003). E7‐632T, ‐760A (T20I, G63S) was more frequently found in Asia, and E7‐793G (T74A) was more frequent in Africa ( p < 0.001). Variants with T20I and G63S substitutions at E7 conferred a significantly higher risk for cervical intraepithelial neoplasia grade III and invasive cervical cancer compared to other HPV58 variants (odds ratio = 4.44, p = 0.007). In conclusion, T20I and/or G63S substitution(s) at E7 of HPV58 is/are associated with a higher risk for cervical neoplasia. These substitutions are more commonly found in Asia and the Americas, which may account for the higher disease attribution of HPV58 in these areas. Abstract : What's new? For unknown reasons, human papillomavirus (HPV) 58 accounts for a significant proportion of cervical cancers in East Asia and parts of Latin America, but it is uncommon elsewhere. In this study, the authors analyzed the E6 and E7 genes from HPV58 samples from around the world. They found that patients with an HPV58 variant containing T20I and G63S substitutions in E7 had a greater risk of developing cancer. This variant was also more prevalent in Asia than in other regions, and may therefore help to explain the higher disease burden observed in this region.